UPAYA PENINGKATAN AGROINDUSTRI PERKOTAAN MELALUI KAJIAN KEANEKARAGAMAN TANAMAN PEKARANGAN DI KABUPATEN MAGETAN - Mustika Wardhani, Ratna (JURNAL AGRI-TEK, 2018)
Empowerment of yard which is solution of problem of limited agricultural land experienced by urban society. The problem of agroindustry up to now is always faced with obstacles of supply management and quality of raw materials. The expected research objectives are to identify and assess the types of crops grown on the yard and determine the priority of agro-industrial development potential in Magetan City. The method used in this research is descriptive method implemented on some respondents who empower the yard as a provider of raw materials agroindustry. Location samples are chosen purposively with non-random methods and are selected on the basis of consideration. The location chosen in this research is Magetan City Region. while the method of data analysis in determining the priority of agroindustry potential that is used is Exponential comparison method (MPE). The results of the research are as follows: (a). In the city of Magetan, the use of yard is done by the cultivation of Fruit, Vegetable and Medicinal Plants (TOGA) plants, (b). Priorities 1 to 3 which are potential for development as raw materials of agroindustry are as follows: Plant Fruit Type namely Mango, Melinjo and Banana, Types of Vegetable Crops ie Chilli, Sledri and Tomato, Types of Medicinal Plants (TOGA) ie Ginger, Turmeric and Pandanus. (c) Type of Agroindustry Processed Products that can be developed in Magetan City according to the potential of cultivation in the yard is as follows: Type of Fruit Crop can be processed into Various Chips, Dodol, Syrup, Fruit Extract, etc., Types of Vegetable Crops can be processed into Various Kripik, Sambel Pecel, Saos etc, Types of Medicinal Plants can be processed into Candy, Syrup, Processed Seasonings, Jamu, Instant Ginger etc. Keywords: Agroindustry, Yard, Plant Diversity